2006
DOI: 10.2164/jandrol.05103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemotherapeutic Agents for Testicular Cancer on the Male Rat Reproductive System, Spermatozoa, and Fertility

Abstract: Testicular cancer is the most common cancer affecting men of reproductive age. Advances in treatment of the disease, which include the coadministration of bleomycin, etoposide, and cisplatinum (BEP), have brought the cure rate to over 90%. This high cure rate, coupled with the young age of patients, makes elucidation of the impact of the treatment on reproductive function, fertility, and progeny outcome increasingly important. The goal of this study was to determine the effects of BEP, in doses analogous to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
71
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 49 publications
10
71
2
3
Order By: Relevance
“…These findings are in accordance with those of previous studies (6,7). The adverse effects of chemotherapeutics on testicular function have been demonstrated previously in animal models (8,9,28,29). The exposure of male rats to BEP caused the degeneration of germ cells, the formation of multinucleated giant cells, the shedding of immature germ cells within the lumen, Sertoli cell vacuolization, and increased apoptosis, especially of spermatogonia and spermatocytes (29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in accordance with those of previous studies (6,7). The adverse effects of chemotherapeutics on testicular function have been demonstrated previously in animal models (8,9,28,29). The exposure of male rats to BEP caused the degeneration of germ cells, the formation of multinucleated giant cells, the shedding of immature germ cells within the lumen, Sertoli cell vacuolization, and increased apoptosis, especially of spermatogonia and spermatocytes (29).…”
Section: Discussionsupporting
confidence: 92%
“…Improved chemotherapeutic regimens for testicular cancer and HL have augmented survival (4,5). Unfortunately, these treatments are associated with a negative impact on reproductive health in men (6,7) and detrimental effects on testicular function, including a decrease in fertilization rate and pregnancy losses in animals (8)(9)(10)(11). Chemotherapy produces azoospermia or severe oligozoospermia in some patients with cancer (6,7) and may have a negative impact on sperm DNA integrity.…”
mentioning
confidence: 99%
“…Experimental use of the co-administration of bleomycin, etoposide, and cisplatinum (BEP) treatment in doses related to the ones used in testicular cancer patients induces DNA strand breaks and increments the susceptibility of sperm to DNA denaturation as studied by the acridine orange assay. It is noted that while these alterations do not compromise fertility in experimental animals, they might be responsible for early death of newborn pups sired by treated male rats, as demonstrated in a previous study (Bieber et al, 2006). These results coincide with similar reports of sperm aneuploidies, spontaneous abortions, and stillbirths in testicular cancer patients treated with CT (De Mas et al, 2001).…”
supporting
confidence: 90%
“…In the same way, modern life style and use of underwear has been proposed to produce an elevated scrotal temperature that may cause germ cell apoptosis, akin to transient (438C for 15 min) heat stress in testis (Hikim et al, 2003;Jung and Schuppe, 2007). Germ cells undergoing meiosis (named spermatocytes) are highly sensitive to DNA damage and other insults such as heat shock, ionizing radiation, growth factor deprivation, and impact of chemotherapeutic agents (Russell et al, 2004;Meachem et al, 2005;Bieber et al, 2006;Lizama et al, 2009). In this way, we have recently shown that etoposide, a topoisomerase-II inhibitor, which induces DNA damage, induces a massive apoptosis of spermatocytes in 21-day-old rats, 24 h after treatment (Ortiz et al, 2009).…”
mentioning
confidence: 99%